(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In today world innovation in all the field has become an important part, prefabrication has become an important technology in construction field. Prefabrication is the practice of assembling components of a structure or building in a factor or other manufacturing sites, and transporting complete assemblies or sub-assemblies to the construction site where the structure is to be located. The term is used to distinguish this process from the more conventional construction, practice of transporting the basic materials to the construction sites where all assembly is carried out. The term prefabrication can apply to any construction method where a significant part of the construction takes place offsite in factory that produced relatively large, complex pieces that are then assembled at the site into the finished building. There are various technologies available worldwide for using prefabricated construction methods, almost all technologies try to reduce cost and time, prefabrication method gives possibilities to the designers for assembling their structures in a short period of time. But the main disadvantage of prefabricated construction is the cost of the building. Use of this technology although reduces the time of construction but fails in reducing the cost, therefore there is a limitation in the usage of prefabrication in the construction industry. Prefabrication technologies could be used more in building construction if the disadvantages of prefabrication are removed and more suitable ways are detected. In this paper, literature review, brief introduction about prefabricated elements and its cost comparison with conventional methods of construction has been given. However, if the disadvantages are overcome and suitable ways are detected it has a wide scope in future.